Green STEAM-H pedagogy with eco-mathematical literacy: a developmental framework for sustainability-oriented education - Fatimah, Ai Tusi; Isyanto, Agus Yuniawan; Erlin, Euis; Sunaryo, Yoni; Zamnah, Lala Nailah; Ruswana, Angra Meta; Solihah, Sri (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
This study proposes a conceptual framework for Green STEAM-H Pedagogy, integrating Eco-Mathematical Literacy as an approach to sustainability-oriented education. The framework responds to the growing need for educational models that systematically connect sustainability values, interdisciplinary learning, and analytical competencies in addressing complex environmental challenges. It synthesizes three key dimensions: green pedagogy as a value-oriented foundation, STEAM-H (Science, Technology, Engineering, Agriculture, Mathematics, and Health) as an interdisciplinary structure, and eco-mathematical literacy as a central analytical component. The framework is operationalized through a developmental progression consisting of three stages: eco-awareness, eco-integration, and eco-transformation. These stages represent a structured pathway through which learners develop ecological understanding, integrate knowledge across disciplines, and apply their competencies in sustainability-oriented actions. In addition, a pedagogical model is proposed to translate the framework into classroom practice by aligning instructional strategies, learning activities, and expected outcomes. This study contributes to the literature by offering a coherent and operationalizable model that bridges the gap between sustainability theory and educational practice. The framework highlights the role of eco-mathematical literacy in supporting data-driven reasoning and decision-making within interdisciplinary learning contexts. It also provides implications for curriculum development, pedagogy, and assessment in fostering transformative and future-oriented learning.